Desenvolvimento e instrumentação de um sistema de fluorescência com alta resolução espacial e temporal - Gambarotto, Tiago Bonicelli (Universidade Federal de São Carlos, 2025)
Historically, the studies of the electronic states of matter has led to a series of scientific discoveries across various research domains. The interaction of electromagnetic radiation with matter is a fundamental basis for several experimental techniques that investigate the electronic structure and the timescales of dynamic processes. Specifically, fluorescence spectroscopy and time-resolved fluorescence spectroscopy play a crucial role in studying these processes. Fluorescence spectroscopy reveals information about the sample’s electronic structure, while time-resolved fluorescence observes the temporal evolution of excited states. Due to the importance of these studies, the focus of this work is on the implementation of these techniques using a tunable laser source and a high temporal resolution detector (1 ps), operating over a wide spectral and temperature range. The tunable laser allows for selective exploration of different electronic states, and the high temporal resolution captures ultrafast events. This approach will advance the understanding of electronic states and dynamic processes in matter, providing a powerful experimental tool for various research groups.
Development and instrumentation of a fluorescence system with high spatial and temporal resolution
Keywords: Fotoluminescência; Alta resolução espacial e temporal; Óptica não linear; CIENCIAS EXATAS E DA TERRA::FISICA